A mitotic function for the high-mobility group protein HMG20b regulated by its interaction with the BRC repeats of the BRCA2 tumor suppressor - Lee, M; Daniels, M; Garnett, M; Venkitaraman, A (2011)
The inactivation of BRCA2, a suppressor of breast, ovarian and other epithelial cancers, triggers instability in chromosome structure and number, which are thought to arise from defects in DNA recombination and mitotic cell division, respectively. Human BRCA2 controls DNA recombination via eight BRC repeats, evolutionarily conserved motifs of 35 residues, that interact directly with the recombinase RAD51. How BRCA2 controls mitotic cell division is debated. Several studies by different groups report that BRCA2 deficiency affects cytokinesis. Moreover, its interaction with HMG20b, a protein of uncertain function containing a promiscuous DNA-binding domain and kinesin-like coiled coils, has been implicated in the G2-M transition. We show here that HMG20b depletion by RNA interference disturbs the completion of cell division, suggesting a novel function for HMG20b. In vitro, HMG20b binds directly to the BRC repeats of BRCA2, and exhibits the highest affinity for BRC5, a motif that binds poorly to RAD51. Conversely, the BRC4 repeat binds strongly to RAD51, but not to HMG20b. In vivo, BRC5 overexpression inhibits the BRCA2-HMG20b interaction, recapitulating defects in the completion of cell division provoked by HMG20b depletion. In contrast, BRC4 inhibits the BRCA2-RAD51 interaction and the assembly of RAD51 at sites of DNA damage, but not the completion of cell division. Our findings suggest that a novel function for HMG20b in cytokinesis is regulated by its interaction with the BRC repeats of BRCA2, and separate this unexpected function for the BRC repeats from their known activity in DNA recombination. We propose that divergent tumor-suppressive pathways regulating chromosome segregation as well as chromosome structure may be governed by the conserved BRC motifs in BRCA2. © 2011 Macmillan Publishers Limited All rights reserved.